1985
DOI: 10.1007/bf00033569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium sulfate on in vitro organogenesis of tobacco callus

Abstract: Abstlaet. Callus of tobacco (Nicotiana tabacum L. cv. Wisconsin 38) was grown on callus-proliferating (CP) and shoot-forming (SF) media with elevated sodium sulfate (Na: SO,) concentrations either in the light or dark for more than one year. An increase in Na2SO 4 concentration resulted in a decrease in callus growth index, an increase in percent dry weight of callus tissues grown on both media, and a decrease in both number of caUi forming shoots and number of shoots per callus in SF medium. The CP callus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…When tobacco cells are grown on salt they lose water [2], experience an increase in water and osmotic potentials [2,6,15], and accumulate ions and metabolites such as proline and reducing sugars [6,21]. Proliferation of salt tolerant cells, which may also have other phenotypic characteristics, is also favored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When tobacco cells are grown on salt they lose water [2], experience an increase in water and osmotic potentials [2,6,15], and accumulate ions and metabolites such as proline and reducing sugars [6,21]. Proliferation of salt tolerant cells, which may also have other phenotypic characteristics, is also favored.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with NaCl-grown callus [2,6,21,22] have not revealed a similar organogenic response. Our physiological studies were undertaken using CP medium, since addition of Na 2SO 4 promotes adventitious shoot initiation [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For control I cultures, shoot tips were transferred to 125 cm^ Erlenmeyer flasks each containing 40 cm^ shoot-proliferating (SP) medium described below and subcultured monthly. Shoots arising from callus grown on callus-proliferating medium in the presence of Na2SO4 as previously described (Pua et al, 1985) were also selected and grown on SP medium supplemented with 1 % w/v Na2SO4. These gave rise to plants with different degrees of Na2SO4 tolerance (see Results section).…”
Section: Culture Initiationmentioning
confidence: 99%